Using Digital Learning Media Applications In Introducing Marine Education To Children - Yosita Nadila Rahmi (Jurnal Syntax Admiration, 2022)
In limited circumstances, the role of educators is very central to creating an atmosphere and learning achievement. education is important to be introduced from an early age so that children can grow up living with their love of being a maritime nation. The growth of maritime values ​​can foster identity in children. The role of PAUD as an educational institution in instilling a maritime spirit is one of them by implementing maritime learning content based on what is in the 2013 PAUD curriculum. Maritime education has material content that cannot be explained abstractly in early childhood. So that is helping the learning and learning process that takes place effectively and efficiently, interesting learning resources are needed. An interesting learning resource today is an active and interactive learning resource by collaborating with Information and Communication Technology (ICT) audio and visual. This study uses the method of literary analysis and implementation in children aged 5-6 years. The results of the study show that ICT collaboration in maritime learning in early childhood affects the learning process that is interesting, effective, interactive, and encourages children's interaction and participation. This facilitates the golden age that is being experienced by children so that they can support, stimulate and develop the various multi-intelligence potentials of children so that they can interpret maritime education, especially in the 21st century